Pharmacological rescue of nociceptive hypersensitivity and oxytocin analgesia impairment in a rat model of neonatal maternal separation. Issue 12 (December 2018) - Melchior, Meggane; Juif, Pierre-Eric; Gazzo, Géraldine; Petit-Demoulière, Nathalie; Chavant, Virginie; Lacaud, Adrien; Goumon, Yannick; Charlet, Alexandre; Lelièvre, Vincent; Poisbeau, Pierrick
Abstract : Abstract: Oxytocin (OT), known for its neurohormonal effects around birth, has recently been suggested for being a critical determinant in neurodevelopmental disorders. This hypothalamic neuropeptide exerts a potent analgesic effect through an action on the nociceptive system. This endogenous control of pain has an important adaptive value but might be altered by early life stress, possibly contributing to its long-term consequences on pain responses and associated comorbidities. We tested this hypothesis using a rat model of neonatal maternal separation (NMS) known to induce long-term consequences on several brain functions including chronic stress, anxiety, altered social behavior, and visceral hypersensitivity. We found that adult rats with a history of NMS were hypersensitive to noxious mechanical/thermal hot stimuli and to inflammatory pain. We failed to observe OT receptor–mediated stress-induced analgesia and OT antihyperalgesia after carrageenan inflammation. These alterations were partially rescued if NMS pups were treated by intraperitoneal daily injection during NMS with OT or its downstream second messenger allopregnanolone. The involvement of epigenetic changes in these alterations was confirmed since neonatal treatment with the histone deacetylase inhibitor SAHA, not only normalized nociceptive sensitivities but also restored OT receptor–mediated stress-induced analgesia and the endogenous antihyperalgesia in inflamed NMS rats. There is growing evidence in the literature that early life stress might impair the nociceptive system ontogeny and function. This study suggests that these alterations might be restored while stimulating OT receptor signaling or histone deacetylase inhibitors, using molecules that are currently available or part of clinical trials for other pathologies. Abstract : Supplemental Digital Content is Available in the Text.Maternal separation renders adult rats hypersensitive to noxious stimuli and incapable to recruit oxytocin analgesic controls. Rescue is achieved by neonatal treatments with oxytocin, allopregnanolone, or histone deacetylase inhibitors.